Impacts of Solar Home Systems in Rural Areas: A Case Study in Bangladesh - Era, Samiha Tasnim (Technium Sustainability, 2024)
Access to electricity is important for development in general, but access at low costs is a vital tool of economic and social development, especially for those locations that lie very far from the grid. The present study investigates the impacts of solar home systems in a rural area of Bangladesh, focusing on the ways in which the adoption of SHS transforms household livelihoods. It has improved the lives of the community members through an affordable and reliable source of electricity that allowed enhanced lighting and security, increased educational opportunities, empowerment of women, reduced reliance on harmful energy sources, increased economic productivity, environmental sustainability, human relationships and well-being. These studies emphatically underscore the fact that the biggest challenge remains affordability: in most instances, SHS is accessed through family savings or loans from NGOs. In spite of these barriers, SHS has conventionally been portrayed as an empowering tool that enhances the quality of life and aids in fulfilling the goals of sustainable development in rural areas. The paper concludes by relating conventional energy sources with a comparison, emphasizing broader benefits and possible long-term potentials for SHS in tackling energy poverty within rural Bangladesh.